2001
DOI: 10.1177/13670069010050010101
|View full text |Cite
|
Sign up to set email alerts
|

Towards a description of trilingual competence

Abstract: AcknowledgementsMy thanks are due to the two anonymous reviewers for their helpful comments and suggestions. I also thank Dr Rosa Manchón of the University of Murcia who undertook a critical revision of a previous draft. AbstractMost studies involving trilingualism have been carried out within the theoretical framework of bilingualism research. No attempt has been made to delimit trilingualism as a concept in its own right, and often it has been assumed to be an extension of bilingualism. In young children, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 21 publications
2
73
0
3
Order By: Relevance
“…It is vital to meditate and negotiate their metalinguistic stances which could open some venues for us to reach a transcendental understanding of the languages they learned and the different realities they establish (Hadi-Tabassum, 2006). Some researchers indicated that research in trilingualism is carried out in the theoretical vein of bilingualism and there are no real efforts to delimit trilingualism in its own right (Aronin, & Hufeisen, 2009;Hoffmann, 2001;Njurai, 2016). Although certain salient similar features could be noticed in both bilinguals and trilinguals (Aronin & Hufeisen, 2009) there are some distinct features that could be observed in trilingualism as it was evident in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is vital to meditate and negotiate their metalinguistic stances which could open some venues for us to reach a transcendental understanding of the languages they learned and the different realities they establish (Hadi-Tabassum, 2006). Some researchers indicated that research in trilingualism is carried out in the theoretical vein of bilingualism and there are no real efforts to delimit trilingualism in its own right (Aronin, & Hufeisen, 2009;Hoffmann, 2001;Njurai, 2016). Although certain salient similar features could be noticed in both bilinguals and trilinguals (Aronin & Hufeisen, 2009) there are some distinct features that could be observed in trilingualism as it was evident in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers indicated that research in trilingualism is carried out in the theoretical vein of bilingualism and there are no real efforts to delimit trilingualism in its own right (Aronin, & Hufeisen, 2009;Hoffmann, 2001;Njurai, 2016). Although certain salient similar features could be noticed in both bilinguals and trilinguals, there are some distinct features that could be observed in trilingualism.…”
Section: Bilingualism Vs Trilingualismmentioning
confidence: 99%
“…It is not ruled out that even more benefits are experienced by trilinguals. As put by Hoffman (2001):…”
Section: Building Multiple Language Representations In Infant Trilingmentioning
confidence: 99%
“…Studies on Trilingual First Language Acquisition (TFLA), that is, on the development of three languages from birth, are either very little systematic in how they report input characteristics, data collection, analyses, etc. (see Quay, 2001, and Hoffman, 2001, for a review); they often amount to a few case studies that explore specific themes such as cross-linguistic influence (Kazzazi, 2011), code-switching after age three (Edwards & Dewaele, 2007;Hoffmann & Stavans, 2007;Stavans & Muchnik, 2008;Stavans & Swisher, 2006), or the relationship between input and development in one language (Barnes, 2006;; or they are anecdotal reports of individual cases of trilingual acquisition at times addressed to the general public (Maneva, 2004;Wang, 2008). In sum, systematic, longitudinal analyses of early trilingualism are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, some researchers have even questioned the very existence of an 'end state' (Dewaele & Pavlenko, 2003;Larsen-Freeman, 2005;Cameron & Larsen-Freeman, 2007;de Bot & Larsen-Freeman, 2011). Furthermore, Hoffmann (2000Hoffmann ( , 2001 examined trilingual competence and concluded that while acquisition, language use, and communicative competence may be roughly the same as in bilinguals, there was evidence of a qualitatively distinct pragmatic competence in terms of linguistic selection, mixing, switching, and borrowing. So far so good, but problems with multi-competence remain: it does not account for acquisition in a socially embedded way, it assumes that speaker and contextual knowledge is homogenous (Franceschini, 2011), and finally, it still subsumes multilingualism into the field of SLA.…”
Section: Changing Directions In Multilingualism Researchmentioning
confidence: 99%